CORRELATION OF ANXIETY AND WORKLOAD AMONG HEALTH PROFESSIONALS IN TOURISM AREA IN DENPASAR, BALI - Wijaya, Putu Austin Widyasari; Evayanti, Luh Gde; Ekayani, Ni Wayan Diana; Ekayanti, Ni Wayan Sri; Setiabudy, Marta (JURNAL WIDYA MEDIKA, 2026)
Health professionals bear high moral responsibilities and face various workplace concerns, such as the risk of disease transmission, the challenge of interacting with diverse patients, the complexity of patient management, and high patient volumes in several health facilities. Previous studies have indicated that high workloads can influence stress levels and disrupt bodily homeostasis. It is hypothesized that healthcare workers with high workloads also exhibit higher levels of anxiety. Consequently, this study aims to determine the relationship between workload and anxiety levels among healthcare professionals, especially those who have been working in the tourism area in Denpasar. This study utilized a cross-sectional method involving healthcare workers in Denpasar employed in outpatient clinics, with data analyzed using Spearman’s correlation test. The instruments employed were the Hamilton Anxiety Rating Scale and the National Aeronautics and Space Administration Task Load Index (NASA-TLX) questionnaire. The results demonstrated that workload has a significant relationship with anxiety among healthcare workers (p = 0.003) with a strong correlation (r = 0.521). These findings are supported by the mechanism of stress hormone secretion via the HPA-axis when individuals encounter work-related stressors or high workloads. In the long term, this condition triggers psychological disorders and anxiety.